2001
DOI: 10.1002/1099-0739(200102)15:2<141::aid-aoc140>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalyzed electrochemical carboxylation of epoxides: mechanistic aspects

Abstract: The electrochemical incorporation of carbon dioxide into epoxides catalyzed by nickel(II) complexes afforded cyclic carbonates in good yields under very mild conditions (p CO 2 = 1 atm, room temperature). Mechanistic and electrochemical studies revealed the cooperative role of reduced nickel species in the activation of CO 2 and the influence of magnesium ions as Lewis acids in the activation of the oxirane ring. Both the presence of nickel catalysts and Mg 2 ions were necessary for the electrocarboxylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Dun ˜ach et al also reported the electrochemical reaction of epoxides with CO 2 in the presence of a nickel complex to afford the corresponding cyclic carbonates under mild conditions. 99 In the present case, however, the use of a volatile organic solvent and a heavy metal catalyst is not necessary to conduct this useful reaction.…”
Section: Electroreductive Coupling Cathodic Reduction Of Benzaldehyde...mentioning
confidence: 94%
“…Dun ˜ach et al also reported the electrochemical reaction of epoxides with CO 2 in the presence of a nickel complex to afford the corresponding cyclic carbonates under mild conditions. 99 In the present case, however, the use of a volatile organic solvent and a heavy metal catalyst is not necessary to conduct this useful reaction.…”
Section: Electroreductive Coupling Cathodic Reduction Of Benzaldehyde...mentioning
confidence: 94%
“…In parallel, the electroreductively formed Ni I species activates CO 2 and mediates the subsequent carboxylation, resulting in ring closure upon bromide elimination. [ 24 , 90b , 90c ] The transformation proceeded with good yields and selectivities for aromatic, benzylic and aliphatic epoxides. The method was also applicable for terminal disubstituted epoxides, resulting in hydroxybenzolactones, although via a different reaction pathway.…”
Section: Electrochemical C−o Bond Activation In Ethersmentioning
confidence: 99%
“…Whereas terminal epoxides led to cyclic carbonates 39 in excellent yields, 69,70 1,1-disubstituted epoxides first reacted through electrocarboxylation of the carbon-halogen bond of 38 followed by the oxirane ring opening. 71 Five-memberedring benzolactones were formed with cyclam as the ligand on nickel, whereas six-membered-ring isocoumarin derivatives were obtained using 2,2 0 -bipyridine (Scheme 22). 68 The analogous insertion of carbon dioxide into aziridines for the synthesis of cyclic carbamates has also been described in Ni I (cyclam)-catalysed reactions.…”
Section: Cyclisation Of Monohalides To Non-activated C-c Double and T...mentioning
confidence: 99%